2004
DOI: 10.1021/jp049086z
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Lithium Absorption in Single-Walled Carbon Nanotubes by Boron Doping

Abstract: The lithium absorption energies and electronic structures of the boron-doped single-walled carbon nanotubes (SWCNT) were investigated using the first-principles calculations. The lithium absorption energies in the B-doped SWCNTs are large negative values, compared with those in the pure SWCNT, whether Li is absorbed at inner sites or at outer sites of the tube walls. The B doping forms an electron-deficient structure in SWCNT, which can effectively accept the electrons from the absorbed Li and stabilize the Li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 62 publications
(24 citation statements)
references
References 34 publications
0
24
0
Order By: Relevance
“…They found that the B-doped MWCNTs increased the Li insertion capacities due to their higher specific surface area, better 3D ordering, larger defect concentration and higher conductivity. It is worth expecting that the doping effects of B in the system of short SWCNT must be much more apparent [33]. The introduction of B into SWCNT should further be investigated, and the effectively enhanced Li absorption performance in B-doped SWCNT systems should be expected.…”
Section: Electronic Structure and Chemical Bonding Of B-or Ndoped Swcntmentioning
confidence: 99%
“…They found that the B-doped MWCNTs increased the Li insertion capacities due to their higher specific surface area, better 3D ordering, larger defect concentration and higher conductivity. It is worth expecting that the doping effects of B in the system of short SWCNT must be much more apparent [33]. The introduction of B into SWCNT should further be investigated, and the effectively enhanced Li absorption performance in B-doped SWCNT systems should be expected.…”
Section: Electronic Structure and Chemical Bonding Of B-or Ndoped Swcntmentioning
confidence: 99%
“…Theoretical investigations have focused on the intercalation of Li in SWCNTs, [23][24][25][26][27][28][29][30][31][32][33][34][35][36] in multiwall carbon nanotubes ͑MWCNTs͒, 9,21,23,37 and the calculation of energy barriers for entry and diffusion of Li inside the tubes. 24,25,27,29,30,[32][33][34][37][38][39] The binding energy of Li to nanotubes of different diameters and chiralities has been obtained in several papers 4,[23][24][25][26][27][28][29][32][33][34][35]37,38,40 using ab initio methods.…”
Section: Introductionmentioning
confidence: 99%
“…Even though pristine CNTs have significant performances so far, Zhou et al attested that boron-or nitrogen-doping could give a constructive change to CNTs [20,21]. Compared with carbon, boron is an electron-deficient element in carbon-based materials, and on the contrary, nitrogen has one more electron than carbon.…”
Section: Carbon Nanotubesmentioning
confidence: 99%
“…Since simple N-doping in carbon nanotubes results in electron-rich structure, and shows negative effect on Li adsorption, N-doped carbon nanotubes are not suitable for LIB anode materials [20][21][22]. CNTs with pyridine-like structure may bring some changes.…”
Section: Carbon Nanotubesmentioning
confidence: 99%